Legal Source Materials In The National Archives - Balan, P (Journal of Malaysian and Comparative Law, 2018)
The purpose of this paper is to introduce the legal researcher to the National Archives of Malaya and to provide some information on the facilities its provides for reference and research. An attempt is also made to provide a rough guie on the legal source materials in its custody.